2004
DOI: 10.3354/ame036227
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cycling and bacterial carbon sources in pristine and impacted Mediterranean seagrass sediments

Abstract: Stable carbon-isotope ratios of bacterial biomarkers were studied in Mediterranean seagrass meadows and macroalgae communities to identify the sources of organic carbon used by the sediment bacteria. Bacteria δ 13 C ratios in pristine sediments vegetated by the seagrass Posidonia oceanica were either similar to the seagrass signal or slightly enriched, suggesting that seagrass detritus was of major importance as a bacterial carbon source. There was a shift in bacterial carbon sources in anthropogenic impacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
92
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 58 publications
6
92
0
6
Order By: Relevance
“…TP content in P. oceanica and unvegetated sediments in Magaluf Bay was 2.9 and 2.4 mmol C g 21 dw, respectively (Holmer et al 2003). Sulfate reduction is significantly higher in P. oceanica sediments than in bare sediments in Magalluf, and total reducible sulfur concentrations in P. oceanica sediments are slightly higher than in bare sediments (Holmer et al 2004). Pore water sulfides concentrations of both communities in Magalluf Bay are not reported by Holmer et al (2003), but in three of the sites of Mallorca Island from this study, higher sulfide concentrations were found in sediments under P. oceanica than in unvegetated sediments.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…TP content in P. oceanica and unvegetated sediments in Magaluf Bay was 2.9 and 2.4 mmol C g 21 dw, respectively (Holmer et al 2003). Sulfate reduction is significantly higher in P. oceanica sediments than in bare sediments in Magalluf, and total reducible sulfur concentrations in P. oceanica sediments are slightly higher than in bare sediments (Holmer et al 2004). Pore water sulfides concentrations of both communities in Magalluf Bay are not reported by Holmer et al (2003), but in three of the sites of Mallorca Island from this study, higher sulfide concentrations were found in sediments under P. oceanica than in unvegetated sediments.…”
Section: Discussionmentioning
confidence: 95%
“…Bare sediments in Magalluf Bay had lower POC and PON content (0.19% and 0.21% POC; 0.017% and 0.030% PON) compared to P. oceanica meadows (0.26% and 0.38% POC; 0.031% and 0.041% PON; Holmer et al 2003Holmer et al , 2004. TP content in P. oceanica and unvegetated sediments in Magaluf Bay was 2.9 and 2.4 mmol C g 21 dw, respectively (Holmer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the second highest C org burial rate in this study (40 6 3 g C org m 22 yr 21 ) was observed in the sediments from Portocolom, where a higher C org sedimentation rate compared to other meadows (i.e., Sta. Maria and Magalluf) has been reported in the past due to high nutrient and organic inputs from the surrounding town, boating activity and a fish farm (Holmer et al 2004;Vaquer-Sunyer et al 2012). Symptoms of eutrophication have been observed in Es Port bay during the summer period (Marba et al 2006; Supporting Information Table SI 1) where sedimentation rates exceeded those measured at the pristine meadows elsewhere in Cabrera National Park (e.g., Sta.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of eutrophication have been observed in Es Port bay during the summer period (Marba et al 2006; Supporting Information Table SI 1) where sedimentation rates exceeded those measured at the pristine meadows elsewhere in Cabrera National Park (e.g., Sta. Maria) (Supporting Information Table SI 2; Holmer et al 2004). In addition, an increase in the accumulation of allochthonous carbon in coastal sediments as a consequence of human pressure increase has been already reported in previous studies (Savage et al 2010), including studies conducted in seagrass meadows (Macreadie et al 2012).…”
Section: Discussionmentioning
confidence: 99%